Comparison of Accelerated VS Standard Ponseti Method in Management of Idiopathic Clubfoot (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To compare the efficacy of accelerated Ponseti vs standard Ponseti method for treatment of idiopathic clubfoot as assessed by Pirani scoring system. Study design: Randomized controlled trial. Method: A total of 80 patients, 40 in each group were randomly allocated to either Group A (Standard Ponseti) or Group B(Accelerated Ponseti). Group A underwent serial manipulations and castings weekly and Group B received manipulations and castings twice weekly. Pirani scoring was documented at presentation, at each cast and at the time of removal of final cast to assess the success of treatment in terms of Pirani score ? 1. Results: 61.3% babies were male. Mean number of casts required was 5.2 in group A and 5.12 in group B. Correction of all deformities was achieved in 95% patients in group A and 90% of patients in group B. This difference was not found to be statistically significant (p=0.396). Conclusion: Accelerated Ponseti method is a good alternative for CTEV requiring shorter time period and with comparable efficacy to standard method.Key words: CTEV, clubfoot, congenital deformity